Diffuse hypertrichosis induced by minoxidil 5% in a child. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
In the case here reported hypertrichosis is due to minoxidil 5%, because the little girl had withdrawn cyclosporin from 3 years and took from several years small doses of prednisone. On the other hand, minoxidil, a piperidine-pyrimidinic derivative used per mouth in hypertension, is responsible for hypertrichosis in 70% of cases. This is why it is used topically in androgenetic alopecia.